The effectiveness of legislative oversight in enhancing executive accountability : a case of the Limpopo Provincial Legislature, South Africa - Thelele, Karabo Cyriel (My University, 2025)
Legislative oversight is a constitutional requirement in the South African system of government for maintaining accountable governance. However, the implementation of this mandate has continued to be a major challenge due to poor performance, maladministration, abuse of state power, and corruption scandals in procurement processes. The purpose of this study is to explore how the legislative oversight enhances executive accountability using the case of the Limpopo provincial legislature. The study has the following objectives: to ascertain the strategies employed by the Limpopo Provincial Legislative Oversight Committee to improve executive accountability, to examine the challenges encountered by the Limpopo provincial legislature in enhancing executive accountability, and to examine the effectiveness of Limpopo provincial legislative oversight to enhance executive accountability. The study adopted a qualitative research case study approach using in-depth interviews with 12 key informants drawn from portfolio, executive and ordinary members of the Limpopo provincial legislature. The findings revealed that oversight committees in Limpopo focus on curbing power abuse by monitoring executive actions through public hearings, meetings, reports, and site visits. The finding highlights that transparency, regular accountability reviews, and public engagement are inconsistently implemented, making it difficult to address executive misconduct in the province. The study recommends, inter alia, allocation of additional funds towards oversight committees and benchmarking with other provinces and international legislatures to enhance oversight strategies
Thesis (MPAM.) -- University of Limpopo, 2025
Keywords: Legislative oversight; Executive accountability; Limpopo Provincial Legislature; South Africa; Legislative oversight -- South Africa -- Limpopo Province; Legislative auditing; Government accountability; Legislative auditing -- South Africa -- Limpopo